Screening for point mutations in the factor VIII gene by denaturing gradient gel electrophoresis - Aksu, A. Anıl. (Thesis (M.S.)- Bogazici University. Institute for Graduate Studies in Science and Engineering, 1994., 1994)
In genetic disorders such as hemophilia A, accurate carrier identification and prenatal diagnosis is achieved by molecular approaches namely linkage analysis and direct identification of mutations: DNA linkage analysis is the major diagnostic approach because of the large size of the FVlll gene causing hemophilia A. However, linkage analysis has a number of limitations such as the requirement of the participation of many family members and the need of an informative and preferably intragenic marker for the family. Family members of five hemophilia A afflicted families that requested carrier identification andlor prenatal diagnosis have been analyzed with three markers that had previously been used in linkage analysis of hemophilia A. In three families expecting mothers were diagnosed as noncarriers by exclusion analysis. The two prenatal diagnosis revealed that one fetus was a normal female and the other one was an affected male. In order to improve the effectiveness of linkage analysis in families afflicted with hemophilia A, the preliminary analysis of a hypervariable (CA), repeat polymorphism located at lntron 13 of the Factor Vlll gene was carried out. Seven families were analyzed using (CA), repeat polymorphisms. In two families carrier identification and prenatal diagnosis carried out with previous markers were confirmed with (CA), repeat analysis. Denaturing ~radienGt el Electrophoresis (DGGE) is one of the screening methods used to identify point mutations rapidly, in large genes. It involves the separation of DNA fragments according to their melting properties in a gel system that contains a linear gradient of DNA denaturants. Partially melted fragments are required for separation of normal and mutant DNA, where mutations fall in the melted region of the fragments. Ten per cent of the FVlll gene was screened by analyzing exons 11, 23, and 24 of 78 Turkish patients. One putative mutation in Exon 11 and two putative mutations in Exon 23 were detected. Partial sequencing of Exon 11 from the patient presumed to have a base change did not reveal any sequence alteration when compared with the sequence of Exon 11 in a normal individual. This work has initiated and established the use of DGGE analysis in screening for mutations in the factor Vlll gene of Turkish patients with the aim of providing accurate prenatal diagnosis and studying the molecular biology of the gene.
Keywords: Hemophilia.; Gel electrophoresis.